PAS-ANSO Strategic Planning for Epidemic and Pandemic Preparedness - Ali, Muhammad; Iqrar, Irum (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Under the ANSO (Alliance of International Science Organizations) collaborative research grants (ANSO-CR-PP-2021-05), we arranged the first event “MAAP-PAS-ANSO hybrid workshop on ecosystem restoration: one-health and pandemics” (June 05, 2022; on the occasion of world environment day) at Pakistan Academy of Sciences, Islamabad. The workshop stresses communication and collaboration for sustainable health (human, animal, and environment) and gauged issues related to the health of the planet. Under the same project, the second event “ANSO-PAS-MAAP conference on the epidemic and pandemic preparedness” (December 05-07, 2022) was organized at the Pakistan Academy of Sciences, Islamabad. The three days event emphasizes more scientific efforts and brainstorming to discuss strategies for controlling the current COVID-19 pandemic as well as future epidemics, pandemics, and emerging pathogens. The conference abstract book highlights the resource persons and their thoughts (in the form of abstracts and their biographies). Selected articles are published as a special issue in the Proceedings of the Pakistan Academy of Sciences: Part B. Life and Environmental Sciences. Moreover, the conference proceedings and recommendations have also been published in the special issue.